Analisis Kritis Terhadap Penerapan Presidential Threshold dalam Pemilihan Umum 2024: Perspektif Hukum Normatif di Indonesia - Alex Cahyono; Anik Iftitah; Ananda Rizki Hidayatullah; Eko Yuliastuti; Weppy Susetiyo (Jurnal Supremasi, 2023)
The minimum requirements for presidential and vice presidential nominations (presidential threshold) in Indonesia ahead of the 2024 General Election (Pemilu) continue to be a source of debate in the context of Constitutional Law. This debate arose due to factors such as allegations that the previous regime which won the election wanted to ensure its position as the determinant of presidential candidates in the next election. Through normative legal research methods, research was produced that this threshold was applied to the 2019 Election through Article 222 of Law Number 7 of 2017 concerning General Elections. This article stipulates that candidate pairs must be proposed by political parties or combinations of political parties participating in the election that succeeded in winning at least 20% of the total seats in the House of Representatives or 25% of the valid national votes in the previous election. This has the potential for the emergence of transactional politics in the formation of political party coalitions that are not based on shared ideology. Empirical facts and experience from the last election show that due to the presidential nomination threshold, the 2019 election produced the same two pairs of candidates as the 2014 election. This indicates that the implementation of the presidential threshold effectively eliminates competitors or potential challengers in the presidential and vice presidential elections, violating the general election principles of honesty and fairness. If this threshold remains, it is likely that the threshold for presidential and vice presidential candidacy will become even higher in the future, strengthening the dominance of transactional politics.